BEBERAPA FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR POH GADING UBUNG DENPASAR - NI RAI ARTINI (Universitas Mahasaraswati K. Mataram, 2023)
income of traders at Poh Gading Market, Ubung, Denpasar. This type of research is a quantitative research, namely a study that aims to obtain evidence of a hypothesis. Data collection was carried out by means of interviews and questionnaires as well as direct observation. The sample used was 60 respondents with a simple random sampling technique (simple random sampling). In analyzing used multiple linear regression analysis techniques. The results showed that by testing the regression coefficient partially (t test) with α = 5%, it showed that the three variables (capital, length of business, and working hours) had a positive and significant effect on the income of traders at Poh Gading Market, Ubung, Denpasar. The results of the F test with α = 5% show that together the variables of capital, length of business and working hours have a significant effect on the income of traders at Poh Gading Market, Ubung, Denpasar.